2022
DOI: 10.1002/ps.7141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the non‐neuronal cholinergic system in the ovary of the oriental armyworm, Mythimna separata Walker (Lepidoptera: Noctuidae)

Abstract: BACKGROUND Acetylcholine (ACh), as a classical neurotransmitter, plays great roles in the nervous system. There is increasing evidence of its non‐neuronal roles in regulating basic cell functions in vertebrates. However, knowledge about the non‐neuronal cholinergic system in insects is scarce. RESULTS A comparative transcriptome analysis was performed to investigate differences in the key molecular components of the cholinergic system between the head and ovary. The results showed that expression levels of mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Data for 2 (Z/E = 73:27). Yield: 57%, white solid; mp 138−140 °C; IR cm −1 (KBr): 3488, 2942, 1652, 1266, 1091; 1 General Procedure for Preparation of Target Compounds 4a−m and 6a−m. A mixture of compound 2 or 3 (0.3 mmol), various amines (0.36 mmol), 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDCI) (0.36 mmol), and hydroxybenzotriazole (HOBt) (0.36 mmol) in CH 2 Cl 2 (5 mL) at room temperature was stirred for 6−22 h. Then, the mixture was diluted with CH 2 Cl 2 (20 mL), washed with brine (10 mL), dried over anhydrous Na 2 SO 4 , and concentrated in vacuo.…”
Section: Synthesis Of Compounds 2 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for 2 (Z/E = 73:27). Yield: 57%, white solid; mp 138−140 °C; IR cm −1 (KBr): 3488, 2942, 1652, 1266, 1091; 1 General Procedure for Preparation of Target Compounds 4a−m and 6a−m. A mixture of compound 2 or 3 (0.3 mmol), various amines (0.36 mmol), 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDCI) (0.36 mmol), and hydroxybenzotriazole (HOBt) (0.36 mmol) in CH 2 Cl 2 (5 mL) at room temperature was stirred for 6−22 h. Then, the mixture was diluted with CH 2 Cl 2 (20 mL), washed with brine (10 mL), dried over anhydrous Na 2 SO 4 , and concentrated in vacuo.…”
Section: Synthesis Of Compounds 2 Andmentioning
confidence: 99%
“…On the other hand, compounds 2 and 3 reacting with different alcohols in the presence of EDCI and DMAP afforded ester derivatives 5a−m and 7a−m. Their structures were determined by 1 H NMR, IR, HRMS, and mp. Moreover, the three-dimensional structure of E isomer of 3 was unambiguously confirmed by single-crystal X-ray diffraction (CCDC: 2054338; Figure 3).…”
Section: Effect Of Concentrations Of Aq Sodium Hydroxide Solutions On...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the rapid development of omics technology has provided excellent platforms for exploring molecular mechanisms underlying biological and physiological processes in cells, tissues, and organisms. , Hence, omics technology was widely applied to analyze functions of the insect fat body. For instance, the fat body of B.…”
Section: Introductionmentioning
confidence: 99%
“…14,18−21 Recently, the rapid development of omics technology has provided excellent platforms for exploring molecular mechanisms underlying biological and physiological processes in cells, tissues, and organisms. 22,23 Hence, omics technology was widely applied to analyze functions of the insect fat body. For instance, the fat body of B. dorsalis was speculated to be involved in immunity, detoxification, and energy metabolism as transcriptomic analysis revealed that a large amount of relevant genes are expressed there.…”
Section: ■ Introductionmentioning
confidence: 99%